Religious Minorities, Islam and the Law: International Human Rights and Islamic Law in Indonesia - Khanif, Al (ICLARS Series on Law and Religion Ser., 2020)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Table of Contents -- Glossary -- 1. Introduction -- 1 The significance of the book -- 2 The book's structure -- Bibliography -- 2. Religious minorities under international human rights law and Islamic law -- 1 The scope of human rights law -- 1.1 The status of minorities in international human rights law -- 1.2 The rights of religious minorities in international human rights law -- 1.3 The significance of protecting religious minorities -- 1.4 The liberal character of international human rights law -- 2 Islam and human rights discourse -- 2.1 Towards an egalitarian Islamic law on religious freedom -- 2.2 The contested concepts of apostasy and heresy in Islamic law -- 2.3 Communitarian Islamic law and religious minorities within Islam -- Bibliography -- 3. The discourse of religion and religious minorities within Islam in a "quasi-theistic secular" Indonesia -- 1 The legal acknowledgement of pluralistic character -- 2 The discourse of Indonesian Islam -- 3 Religious minorities within Islam in the religion and state relationship -- 3.1 The Ministry of Religious Affairs (MORA) -- 3.2 The Indonesian Ulama Council (MUI) -- 3.3 The joint-judiciary committee of religious life (Bakorpakem) -- 4 Perspectives of Islamic organisations on religious minorities within Islam -- 4.1 Nahdlatul Ulama (NU) -- 4.2 Muhammadiyah -- 4.3 Hardline Islamic groups -- 5 Islam within the concept of a quasi-theistic secular state -- Bibliography -- 4. The complex reality of religious minorities within Islam in Indonesia -- 1 The discourse of forum internum and forum externum in international human rights law -- 2 Freedom to embrace and practise religion in Islamic law -- 3 The complex reality of religious minorities within Islam in Indonesia -- 3.1 Officially state-sanctioned enforcement actions.